(untitled) (Indian Journal of Nematology, 2024)
The present studies were undertaken with the objectives of recording the diversity of plant parasitic nematodes in the rhizosphere of the mango and guava at IARI farm. Seven species of plant parasitic nematodes were found in mango and guava orchard. These were Helicotylenchus indicus, Hemicriconemoides strictathecatus, Rotylenchulus reniformis, Hoplolaimus indicus, Mesocriconema sphaerocephala, Tylenchorhynchus mashhoodi and Tylenchulus semipenetrans. Amongst the plant parasitic nematodes in mango orchard H. strictathecatus was in high numbers followed by Helicotylenchus indicus. T. mashhoodi was in low numbers. M. sphaerocephala was recorded for the first time on guava and mango. In guava, Helicotylenchus indicus was having maximum density followed by H. strictathecatus and Hoplolaimus indicus. The identity of citrus nematode, Tylenchulus semipenetrans juvenile from the rhizosphere of guava was confirmed based on the ITS region.